Article New Paradigm for Developing Digital Technology Capabilities for Halal Food Community Enterprises in Three Southern Border Provinces' Special Economic Development Zones (Pattani) to Increase Marketing Opportunity to the ASEAN Community - Suyu, Rutchanee (Al-HIKMAH Journal, 2023)
The research's objectives (1) to examine the body of knowledge and the situation in digital technology (2) to create digital technology innovations; (3) to impart knowledge on the use of digital technology in business for community enterprises in the three southern border provinces' Special Economic Development Zones. It is a qualitative data collection method based on observation, in-depth interview group chat and content analysis. This study was conducted using two groups of Purpose Random Sampling, as follows: 1. Chao Lay Fish Cracker Community Enterprise (Fish Cracker Business Group) 2. Dok Kaew Kue Po Community Enterprises interested in receiving digital technology development training. The study's findings were as follows: (1) Data analysis using SWOT Analysis revealed that the members lacked marketing knowledge. Using a Facebook page for online communication is not a good idea. The product is not yet known. A scarcity of young people who will continue to work in online marketing. Strategy (Marketing Mix: 4Ps - 4Cs) Both groups' products will use fresh ingredients. The price is reasonable given the product's high quality. The distribution channel is the most direct route. There are distributors who sell in front of the factory as well as indirectly. or repeat customers. (2) Both sample groups are prepared and eager to participate in digital marketing training in order to increase sales through the expansion of marketing channels. (3) According to the findings of the training program study, the speakers provided knowledge in online marketing via Facebook, with the speakers and research teams acting as mentors and providing advice all the time via group pages and line groups.